Sex Matters: A Comprehensive Comparison of Female and Male Hearts - St. Pierre, Sarah R.; Peirlinck, Mathias; Kuhl, Ellen (Frontiers in Physiology, 2022)
Cardiovascular disease in females remains under-diagnosed and under-treated. Recent studies suggest that this is caused, at least in part, by the lack of sex-specific diagnostic criteria. While it is widely accepted that the female heart is smaller than the male heart, it is often ignored that it is also disproportionally thinner. This has severe implications on a multitude of cardiac parameters. Here we systematically review and compare the geometric, functional, and structural parameters of female and male hearts, both in the healthy population and in athletes. Our study finds that, compared to the male heart, the female heart has a larger ejection fraction and beats at a faster rate, but generates a smaller cardiac output. It has a lower blood pressure, but produces universally larger contractile strains. Critically, allometric scaling, for example by lean body mass, reduces but does not completely eliminate the sex differences between female and male hearts. Our results suggest that the sex differences in cardiac form and function are too complex to be ignored: The female heart is not just a small version of the male heart. When using similar diagnostic criteria for female and male hearts, cardiac disease in females is frequently overlooked by routine exams, and it is diagnosed later and with more severe symptoms than in males. Clearly, there is an urgent need to better understand the female heart and design sex-specific diagnostic criteria that will allow us to diagnose cardiac disease in females equally as early, robustly, and reliably as in males.